Penerapan Kelas Inspirasi sebagai Media Edukasi Bangun Datar : Mengaitkan Impian Siswa dengan Konsep Matematika di SDN 056024 Dogang (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
The low level of interest and motivation among elementary school students in learning mathematics, particularly in plane geometry topics, remains a common problem. This community service activity aimed to improve students’ interest and understanding of plane geometry concepts through the implementation of the Inspiration Class as an educational medium that connects mathematical material with students’ aspirations. The activity was conducted at SDN 056024 Dogang, Langkat Regency, involving sixth-grade students. The implementation method employed a participatory and educational approach consisting of preparation, implementation, and evaluation stages. The activities included the delivery of plane geometry material, interactive discussions, and a creative project in the form of a “dream tree” using origami shaped into plane figures. The evaluation was performed qualitatively by observing student engagement and interactions in question-and-answer sessions, and analysis of students’ work. The results showed that the Inspiration Class created a more active and enjoyable learning atmosphere, increased student participation, and helped students better understand the concepts and properties of plane figures. In addition, this activity motivated students by linking mathematics learning with future aspirations and professions. Therefore, the Inspiration Class can be considered an effective alternative educational medium for teaching mathematics at the elementary school level.